COMPARISON OF EFFICACY OF TOPICAL TAZAROTENE 0.1% CREAM VS ADEPALENE 0.3% AND BENZOYL PEROXIDE 2.5% IN TREATING ATROPHIC ACNE SCARS - MUSHTAQ, F; KHAN, MR; SALEEM, M; KHAN, A; AMIN, S; MUSHTAQ, I (Biological and Clinical Sciences Research Journal, 2024)
Atrophic acne scars are a common dermatological concern that significantly impacts patients’ self-esteem and quality of life. Topical treatments such as Tazarotene and combinations of Adapalene and Benzoyl Peroxide are often used to improve the appearance of these scars. However, their comparative effectiveness requires further evaluation. Objective: To evaluate the effectiveness of Tazarotene 0.1% cream versus a combination of Adapalene 0.3% and Benzoyl Peroxide 2.5% in treating atrophic acne scars. Methods: This study was conducted in the Dermatology Department of PIMS, Islamabad, from January to June 2024, following approval from the hospital’s ethical committee. A total of 140 participants with atrophic acne scars were enrolled and divided into two groups. Group A received Tazarotene 0.1% cream, while Group B was treated with a combination of Adapalene 0.3% and Benzoyl Peroxide 2.5%, both applied once daily at night. The treatment duration was 12 weeks. The severity of acne scars was assessed using the Global Atrophic Acne Scar Scale (GAASS), and the impact on quality of life was measured using the Quality-of-Life Score. Statistical analysis was performed using SPSS Version 26, with significance set at p < 0.05. Results: The mean age of participants was 40.40 ± 11.24 years. Before treatment, GAASS scores were comparable between Group A (3.70 ± 0.64) and Group B (3.80 ± 0.65, p = 0.36). After 12 weeks, Group A showed significantly greater improvement, with a mean GAASS score of 1.72 ± 0.63 compared to 2.17 ± 0.77 in Group B (p = 0.00). Patient satisfaction was also higher in Group A (7.4 ± 1.5) compared to Group B (6.8 ± 1.7, p = 0.00). The Quality-of-Life Score was slightly higher in Group A (85.3 ± 5.2) than in Group B (82.7 ± 6.1), although this difference was not statistically significant (p = 0.14). Side effects were reported in 17.1% of Group A and 27.1% of Group B (p = 0.15). Conclusion: Tazarotene 0.1% cream was more effective than the combination of Adapalene 0.3% and Benzoyl Peroxide 2.5% in treating atrophic acne scars. Despite no significant difference in quality-of-life improvements between the two treatments, tazarotene patients experienced more significant scar reduction, higher satisfaction, and fewer side effects.